2008
DOI: 10.1111/j.1440-1843.2008.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary haemodynamic changes in patients with severe COPD

Abstract: Worsening gas exchange during exercise and exacerbation in COPD contributes to systemic hypoxemia and restricts the quality of life. However, pulmonary hemodynamics under such conditions are not well understood. We performed right heart catheterization in six patients with severe COPD (%FEV 1 < 50%) during rest, exercise and exacerbation. Pulmonary artery pressure (Ppa) was a little elevated at rest. The Ppa, as pulmonary artery wedge pressure (Pawp) and cardiac index were significantly increased during bicycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…According to pulmonary hypertension guidelines [10] and as suspected, moderately increased PAP on admission was found and then was partially reduced by the exacerbation treatment [4] (Table 4). Similarly to Hanaoka et al [33], but engaging a larger number of patients, we showed that PAP increases during COPD exacerbation. The results of both studies raise the unresolved question of whether there is a need for a larger study with pulmonary artery pressure PAP assessed by right heart catheterisation (RHC).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to pulmonary hypertension guidelines [10] and as suspected, moderately increased PAP on admission was found and then was partially reduced by the exacerbation treatment [4] (Table 4). Similarly to Hanaoka et al [33], but engaging a larger number of patients, we showed that PAP increases during COPD exacerbation. The results of both studies raise the unresolved question of whether there is a need for a larger study with pulmonary artery pressure PAP assessed by right heart catheterisation (RHC).…”
Section: Discussionsupporting
confidence: 88%
“…The observed post-treatment PAPmean and RVSP reduction were independent of dyspnoea, exercise capacity, and blood gasses, which might be the result of oxygen supplementation [32]. In the study by Weitzenblum et al [33] changes of right heart haemodynamics were observed during an episode of peripheral oedema. However, an episode like this could also have been related to right ventricle decompensation, independent of COPD exacerbation.…”
Section: Discussionmentioning
confidence: 81%
“…Data are mean ± SD with exception of symptoms (median and range) BMI body mass index; FVC forced vital capacity; IC inspiratory capacity; TLC total lung capacity; RV residual volume; D L CO lung diffusing capacity for carbon monoxide; Pa arterial partial pressure; EF ejection fraction (by echo-Doppler cardiography); _ VO 2 oxygen consumption; _ VE minute ventilation; MVV maximal voluntary ventilation; HR heart rate end-inspiratory lung volumes (Chabot et al 2001), and (3) higher pulmonary vascular resistance due to compression of juxta-alveolar vessels (Whittemberger et al 1960;Hanaoka et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Probably the only relevant clinical feature to define constancy is whether it is ever reported to disappear once it has developed; intuitively one would imagine that it is as constant as the degree of respiratory failure though this is not supported by published evidence. One small study has shown that pulmonary artery pressure varies with exacerbations and exercise [105]; animal studies also imply phases of remission [106]. There have been few published studies detailing longitudinal changes in sputum bacterial content in stable COPD.…”
Section: Constancy Of Copd Subgroupsmentioning
confidence: 99%